A Cross-Sectional Study to Assess and Correlate Osteoporosis and Periodontitis among Postmenopausal Women: A Dual Energy X-Ray Absorptiometry Study - Vaishali Narayan Mashalkar; Girish Suragimath; Sameer Anil Zope; Siddhartha A Varma (Wolters Kluwer Medknow Publications, 2018)
Background: Periodontitis and osteoporosis are two diseases found worldwide and increase in intensity with increasing age of the patients. The severity of osteoporosis and periodontitis are found to be more in women during menopause. The aim of this study was to assess and correlate osteoporosis and periodontal disease among post-menopausal women. Materials and Methods: The study consisted of 94 postmenopausal women in the age range of 45-65 years. All the women underwent dual-energy X-ray absorptiometry (DXA) scan to measure bone mineral density (BMD) and were graded as normal, osteopenic, and osteoporotic based on the T score obtained. Data regarding patient's educational level, socioeconomic status (SES), and body mass index (BMI) was recorded. A detailed periodontal examination was carried out using clinical parameters such as oral hygiene index (OHI), plaque Index (PI), probing pocket depth , and clinical attachment loss to check the level of periodontitis. The level of osteoporosis was correlated with the level of periodontitis. Results: The DXA scan revealed that four women were normal, 44 were osteopenic and 46 were osteoporotic. There was no association found between BMD and OHI, PI, educational status, SES, and BMI. Slight periodontitis was observed in eight women, moderate periodontitis in 62, and severe periodontitis in 24 women. Result suggests that there was a statistical correlation between periodontitis and osteoporosis (P = 0.045). Conclusion: There is a definite correlation found between the severity of periodontitis and osteoporosis among postmenopausal women. A close cooperation between general practitioners and dentists in early diagnosis and treatment of both the diseases will reduce the risk and morbidity among postmenopausal women.